Validitas E-Book Fisika Terintegrasi Materi Bencana Petir Berbasis Model Discovery Learning - Gema Eferko Putri; Fitrah Ayu; Ahmad Fauzi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
The energy generated by lightning is very large, but it cannot be controlled, causing significant losses and even casualties. To reduce the risk of lightning, a good level of understanding is needed from the public in dealing with lightning disasters. This level of understanding can be changed for the better through education in schools by integrating lightning material into teaching materials for Physics subjects. This study aims to determine the validity of Physics e-book integrated with lightning disaster material based on discovery learning. Research and development (R&D) with the plomp model was used as a method in this study. Products produced in R&D are tested for their validity by experts. The instrument used in this study was a validity questionnaire consisting of five aspects, namely content feasibility, presentation feasibility, language eligibility, graphic feasibility, and media feasibility. The results showed that the Physics e-book integrated with lightning disaster material based on discovery learning was in a valid category so that it could be used in physics learning at school as well as for further research.